Efficient degradation of phenol in aqueous solution by catalytic ozonation over MgO/AC. (August 2020) - Zhou, Lilong; Zhang, Shanshan; Li, Zhengjie; Liang, Xin; Zhang, Zhikun; Liu, Runjing; Yun, Jimmy
Graphical abstract: Highlights: Activated carbon activity for ozonation advanced oxidation can be improved by MgO MgO provides additional active sites for hydroxyl radical generation and phenol degradation The phenol and COD removal ratio reached 88.5% and 83.5%, respectively. Abstract: Phenol is one of the most common and poisonous water pollutants. Treating phenol-containing wastewater has been a challenge in recent years. MgO/Activated Carbon (AC) composites were prepared by the equal volume impregnation method for catalytic ozonation of phenol in water. MgO/AC composites were characterized by ICP, IR, XRD, SEM, TEM, BET and XPS analysis. MgO incorporated in the form of nano-crystal particles on the surface of AC. Prepared MgO/AC shows good catalytic performance for the removal of phenol and COD. Catalyst loading, pH and initial concentration of phenol solution on catalytic ozonation performance were studied. The catalytic performance of AC was significantly improved by the modification with a few amount of MgO. The results showed MgO provides additional active sites for the generation of hydroxyl radicals which is favorable for degradation of organic contaminants. The intermediate products were determined and the possible degradation pathway was put forward. MgO/AC shows a promising way to prepare efficient catalysts for the catalytic ozonation of organic polluted water.